2022
DOI: 10.1101/2022.09.08.22279719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of sleep in the human brain and body: insights from multi-organ imaging genetics

Abstract: Sleep is essential for the health of the brain and heart. Although sleep has been identified as a factor in a few specific clinical outcomes, a systematic analysis of the relationship between sleep and brain/heart and their genetic underpinnings is lacking. Medical images can provide useful clinical endophenotypes for organ structures and functions. Here we present a systematic genetic investigation of sleep-brain/heart connections using multi-modal brain and cardiac images from over 40,000 subjects in the UK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 226 publications
(461 reference statements)
2
3
0
Order By: Relevance
“…Superior parietal regions showed significant associations with the duration of 22 longest sleep bout, depressive symptoms, and cognition. Insomnia and dozing showed few significant associations, in line with previous univariate analyses on the same data 27 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Superior parietal regions showed significant associations with the duration of 22 longest sleep bout, depressive symptoms, and cognition. Insomnia and dozing showed few significant associations, in line with previous univariate analyses on the same data 27 .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, resting state results revealed widespread associations similar to Fan et al 2022 27 , especially for daytime dozing. We found that functional connectivity between the frontoparietal network and in particular the posterior inferior frontal junction (IFJp) and lateral occipital regions was positively associated with duration of longest sleep bout.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations